Laser Acceleration of Electrons in Magnetized Collisionless Plasma - Habeeb, Mohammed A Z; Yahya, Khalid A; Kneoy, Amal M (Al-Nahrain Journal of Science, 2018)
A computational investigation was carried out in the field of laser-plasma interaction to study the acceleration of electrons with non - relativistic velocities in magnetized collisionless plasma. The interaction of a Nd: Yag laser pulse of 25 fs duration and a 5x1015 W/cm2 intensity with a plasma was studied at a plasma electron density ne=1x1018 cm-3 in the presence of an external magnetic field for the three values of the field strength B=60 MG, 70 MG and 80 MG. It was found that the electron acquires a maximum energy of ~ 19 keV during the interaction when an external magnetic field of strength B= 80 MG is applied. The maximum energy of the electron during the interaction reaches ~ 1 keV in the absence of an external magnetic field for the same plasma electron density and laser pulse, after the interaction the maximum energy of the electron reached ~ 15 eV. However, the maximum energy of the electron after the interaction reaches ~ 3 keV when an external magnetic field strength of B= 70 MG is applied. This is due to a sustainable generated laser wakefield of ~ 2x109 V/cm. Thus, it is concluded that an applied external magnetic field assists the acceleration of the electron and can subsidize for a high laser beam intensity.